Environmental factors and the acceptance of youth towards MyEG application: a quantitative empirical investigation - Kamarudin, Syafila; Omar, Siti Zobidah (Human Resource Management Academic Research Society, 2017)
The emergence of MyEG application facilitates in terms of specialized services for Malaysians. Although this application eases users, it is still not completely utilized by the youth. Therefore, this study aims to identify the types of MyEG services used by youth; thus determine the relationship between environmental factors and the acceptance of MyEG application. This study uses a quantitative approach through a survey method using a questionnaire. A total of 396 MyEG users in the Klang Valley have been selected as respondents. Data are analysed using the Statistical Package for Social Science (SPSS) version 22. Two (2) types of statistics are used in this study. They are the Descriptive Statistics and Inferential Statistics. Descriptive statistics is used to identify the mean, percentage and standard deviation. Inferential statistics, on the other hand, is used to describe the relationship between the variables studied. This study found that the type of MyEG service preferred by youth is related to information regarding summons. Through Pearson Correlation test, the result shows that there is a positive and significant relationship between the facility and the performance towards the acceptance MyEG application. This study suggests that MyEG promotes itself in a larger scale medium by utilizing the new media and electronic media so that promotions can be done quickly and widely.